Analysis and proposal of sustainable urban mobility: accessibility to the cultural heritage of the City of Guanajuato; Gto - Fabiola Colmenero Fonseca; Alan Cristian Cruz Ramírez (Vitruvio: International Journal of Architectural Technology and Sustainability)
Through this research and analysis, its intention is to restructure the corporate public transport road network of the Patrimonial city of Guanajuato, based on a systemic approach created by transfer centers and avoiding vehicular traffic. To make the historical center an available, safe, and fast space, with less environmental impact and friendly, we pretend to change the structure of the city. Mobility is a necessity in cities, but it is also a right; it occupies a central role in society while allowing communication, economic activity, and integrating spaces and events; It is needed for all people to access the essential goods and services of a dignified life. The method of analysis that considered is Urban Sustainability as a set of systems, which explains that anyone who presents a problem produces an imbalance in the rest. Therefore, the Urban Sustainability Index (ISU) should understand as a degree achieved by the city to maintain the balance of all systems present in urban life. The elements used were: historical analysis, photographic records, public transport routes, diagrams of vehicle flows, and previous drafts. Its scope changes road capacity and accessibility, quality of life, sustainability, economic, social viability, equity, and quality of the environment. This project is aimed at improving and developing the infrastructure with a set of economically profitable actions. It proposes that short and medium-term actions contribute to a longterm vision and strategy.